Do Sharpshooters From Around the World Produce the Same EPG Waveforms? Comparison of Waveform Libraries From Xylella fastidiosa (Xanthomonadales: Xanthomonadaceae) Vectors Kolla paulula (Hemiptera: Cicadellidae) From Taiwan and Graphocephala atropunctata From California. Issue 4 (17th July 2020) - Backus, Elaine A; Shih, Hsien-Tzung
Abstract: When an exotic invasive species is a vector-borne plant pathogen, vector feeding behavior must be studied to identify potential host plant range and performance of specialized pathogen transmission behaviors. The most rigorous tool for assessing vector feeding behavior is electropenetrography (EPG). Xylella fastidiosa Wells et al. is a gram-negative bacterium native to the Americas, where it is the causal agent of lethal scorch-type diseases such as Pierce's disease (PD) of grapevines. In 2002, a PD strain of X. fastidiosa invaded Asia for the first time, as confirmed from grape vineyards in Taiwan. Kolla paulula (Wallker), a native Asian species of sharpshooter leafhopper, was found to be the primary vector in Taiwanese vineyards. This study used an AC-DC electropenetrograph to record stylet probing behaviors of K. paulula on healthy grapevines. The main objective was to create an EPG waveform library for K. paulula . Waveform description, characterization of R versus emf components (electrical origins), and proposed biological meanings of K. paulula waveforms are reported. In addition, comparison of K. paulula waveforms with those from the most efficient, native vector of X. fastidiosa in California vineyards, Graphocephala atropunctata, is also reported. Overall, both species of sharpshooters had similar-appearing waveforms. Five new findings were identified, especially that the previously described but rare waveform subtype, B1p, was extensively produced in K. paulula recordings. Sharpshooter waveforms from species worldwide share a high degree of similarity. Thus, EPG methods can be rapidly applied to potential vectors where X. fastidiosa is newly introduced.